Curcumin enhances the anti-cancer efficacy of paclitaxel in ovarian cancer by regulating the miR-9-5p/BRCA1 axis - Liu, Yuwan; Shen, Zhangjin; Zhu, Tingjia; Lu, Weiguo; Fu, Yunfeng (Frontiers in Pharmacology, 2023)
Background: Patients with late-stage ovarian cancer still have a very poor prognosis due to chemotherapy resistance. Curcumin has been shown to synergistically enhance the therapeutic effects of multiple chemotherapeutic agents, but the potential involvement of curcumin in ovarian cancer is largely unknown. This study aimed to investigate whether curcumin has synergistic anti-cancer effects with paclitaxel in ovarian cancer and its underlying mechanism. Methods: Ovarian cancer cell lines (SKOV3 and A2780) were treated with curcumin, alone or combined with paclitaxel. Cell viability, colony formation, EdU incorporation assays, and flow cytometry were used to assess cell proliferation, apoptosis, and cell cycle progression. The cytotoxic synergistic effect of curcumin and paclitaxel was detected by Calcusyn software. RNA immunoprecipitation assay was used to verify the interaction between miR-9-5p and BRCA1. qRT-PCR and Western blot were performed to detect gene and protein expression. Results: We found that curcumin and paclitaxel synergistically inhibited proliferation and promoted apoptosis in ovarian cancer cells. Furthermore, curcumin and paclitaxel combination resulted in decreased miR-9-5p expression and increased BRCA1 expression. Functionally, miR-9-5p overexpression counteracted the synergistic effect of curcumin and paclitaxel on cell proliferation and apoptosis by targeting BRCA1. Meanwhile, in vivo experiments revealed that curcumin and paclitaxel combination dramatically suppressed the growth of transplanted tumors, while miR-9-5p mimics eliminated the growth inhibition of xenografts induced by the combined treatment. Conclusion: Curcumin enhanced the anti-cancer efficacy of paclitaxel in ovarian cancer by regulating the miR-9-5p/BRCA1 axis. These findings provide strong evidence for clinical investigation of curcumin and paclitaxel combination as a novel strategy for ovarian cancer patients, and identify miR-9-5p and BRCA1 as key targets for regulating sensitivity to this therapy.